If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 628 = -26 + 100y Solving 628 = -26 + 100y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-100y' to each side of the equation. 628 + -100y = -26 + 100y + -100y Combine like terms: 100y + -100y = 0 628 + -100y = -26 + 0 628 + -100y = -26 Add '-628' to each side of the equation. 628 + -628 + -100y = -26 + -628 Combine like terms: 628 + -628 = 0 0 + -100y = -26 + -628 -100y = -26 + -628 Combine like terms: -26 + -628 = -654 -100y = -654 Divide each side by '-100'. y = 6.54 Simplifying y = 6.54
| 628=-26x+100y | | (6s+5p)(6s-5p)= | | 628=-26x+100 | | 8x-1=2x+8 | | y=-2.5x^2+17.5x+161 | | y=-2.5x^2+17.5x+61 | | (x-9)(x-1)+7=0 | | x=x-3-34+57/2+2-3/4 | | 6+9=98 | | x=x-3-34+57 | | x-23=x-3-34+57 | | 5+5s=20 | | 5r-4=40 | | -2(3x+4)-10=0 | | 8a-5=2a+7 | | -4(x+5y)+6(5x+y)= | | x=1+3-(56-5)2+4-3/4 | | 4(x+1)=9x-1 | | x=1+3-(56-5)2+4 | | 18-3x=-9 | | 12c+6=87 | | 2m-9m=-77 | | x=1+3-56-7*8 | | 9n+3-8n=8-14 | | (x+6)(x+4)=22 | | (4u-6)(8-u)=0 | | 2x-1=32 | | 92x=27 | | 7x^2+6x+3=0 | | x+1=-1+-5 | | 5x^2+7+2=0 | | -3b(2a-3b)+6(-6ab+25b)= |